Proceedings of the 30th Annual ACM Symposium on Applied Computing 2015
DOI: 10.1145/2695664.2695904
|View full text |Cite
|
Sign up to set email alerts
|

A supervised learning approach to detect subsumption relations between tags in folksonomies

Abstract: The lack of hierarchical relations in the tag space of social tagging systems may diminish the ability of users to find relevant resources. Many research works propose to overcome this problem by constructing hierarchies of tags automatically by means of heuristic algorithms. These hierarchies encode subsumption relations between pairs of tags and can be used for improving browsing and retrieval of resources. In this paper, we cast the problem of subsumption detection between pairs of tags as a pairwise classi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 16 publications
0
15
0
Order By: Relevance
“…The former downscales non-event data to match the number of safety threats recorded, while the latter upscales the number of safety events to match the remainder of the data set. Undersampling is achieved through the use of cluster centroids [31], random sampling, and Tomek links [32], whereas oversampling is instituted via Adaptive Synthetic (ADASYN) method [33], Synthetic Minority Oversampling TEchnique (SMOTE) [34], and Synthetic Minority Over-sampling Technique for Nominal and Continuous (SMOTE-NC) methods. These methods are all applied on feature vector matrices and the best performers are chosen for further hyperparameter tuning and cross-validation.…”
Section: Classificationmentioning
confidence: 99%
“…The former downscales non-event data to match the number of safety threats recorded, while the latter upscales the number of safety events to match the remainder of the data set. Undersampling is achieved through the use of cluster centroids [31], random sampling, and Tomek links [32], whereas oversampling is instituted via Adaptive Synthetic (ADASYN) method [33], Synthetic Minority Oversampling TEchnique (SMOTE) [34], and Synthetic Minority Over-sampling Technique for Nominal and Continuous (SMOTE-NC) methods. These methods are all applied on feature vector matrices and the best performers are chosen for further hyperparameter tuning and cross-validation.…”
Section: Classificationmentioning
confidence: 99%
“…However, the features may not be fine-grained enough to represent the topic information in social tags. [40] combined several popular co-occurrence based feature extraction mechanisms to develop a binary classifier. The mechanisms considered included support and confidence [41], cosine similarity, set inclusion and generalisation degree [35], mutual overlapping [9] and graph-based taxonomy search adapted from [26].…”
Section: Knowledge Discovery From Social Tagging Datamentioning
confidence: 99%
“…Another class of method employs machine learning techniques, especially supervised learning, to predict relations. Research in this line also leverages co-occurrence features [40] and usually relies on specific contents from the tagged resources [49].…”
Section: Introductionmentioning
confidence: 99%
“…It is demonstrated that mutual overlapping performs well on the dataset collected from the e-business website Taobao 10 . The two metrics, inclusion-generalization metric and mutual overlapping, are later used as two of the features for the supervised learning approach in [41].…”
Section: ) Set Theorymentioning
confidence: 99%
“…A binary classification approach has been proposed in [41]. Features are extracted based on association rule mining, similarity measures, inclusion and generalization measures [40], mutual overlapping [41] and taxonomy search [34]. The positive and negative classes are labeled using WordNet and ConceptNet 11 .…”
Section: ) Machine Learningmentioning
confidence: 99%